Diagnóstico de la variante conductual de demencia frontotemporal basado en estadios clínicos adaptado para países con baja educación: el caso de Perú - Custodio, Nilton (2023)
Frontotemporal dementia (FTD) is a widely recognized neurodegenerative condition in people under 65 years old. The diagnosis of behavioral variant FTD (bvFTD) is based on a comprehensive clinical assessment, complemented by a multidimensional assessment (neurological, cognitive, neuropsychiatric, biomarker and brain imaging) adapted and validated to the population to be studied; however, despite its increasing prevalence in Latin America and the Caribbean, there is a need for standardized tools and consensus for the bvFTD diagnosis. The manuscript attempts to approximate the approach for the diagnosis of bvFTD in the setting of low and middle-income countries, including Peru.